Development of Knowledge Test Instruments of Prospective Bachelor of Biological Education Based on TPACK and KKNI Framework - Rabia Hidayanti Arnan; Evi Suryawati; Imam Mahadi (Universitas Riau, 2021)
This research is a descriptive study that aims to produce a test instrument for the knowledge of candidates for Biology Education undergraduate candidates for the Technologhy Pedagogy and Content Knowledge (TPACK) and Indonesian National Qualifications Framework. The study was a development with plomp models conducted at the stage of development. Data collection was done by validation and testing. Validation aims to look at the alignment of experts' opinions, while testing serves to see the handling of the problem by analyzing the test results. Data obtained from test results analysis using rasch modelling with the help of the winstep software. The results of the analysis are in the form of the value of reliability, unidimensionality, level of difficulty, distinguishing power, distractor and person - item map. The results showed that the number of valid questions was 63 items, the number of questions that were invalid or not accepted was 17 items. Invalid questions must be followed up in order to produce a good knowledge test instrument so that it can be used in measuring the mastery of TPACK for prospective teachers and biology teachers.